Students’ Perception in Instagram-Assisted Vocabulary Learning with Vocabulary Self-Collection Strategy - Verawati Verawati; Elih Sutisna Yanto; Wahyudin Fitriyana (International Journal of Education, Information Technology, and Others, 2021)
The objective of this research was to investigate senior high students' perception on learning survival vocabularies through Instagram-assisted Vocabulary Self-Collection Strategy. This research provides two research questions: (1)In what ways Vocabulary Self-Collection Strategy and Instagram facilitate students in learning vocabulary? (2)What is the students’ responds toward the VSS project with Instagram assisted? The study was conducted by using classroom action research as the research design. The participants of this study were the senior high school students majoring social program in Karawang. The instruments used in this study were semi-structure interview for students, reflective journal and students’ VSS chart. The findings of this study found three main themes regarding to the students’ perception on Instagram-assisted Vocabulary Self-collection Strategy: (1)Instagram-assisted Vocabulary Self-collection Strategy Enhance Students’ Vocabulary, (2)Instagram-assisted Vocabulary Self-collection Strategy help Students’ Comprehension on Vocabulary, (3)The Challenges of Vocabulary Self-collection Strategy in learning vocabulary. The result implies students can consider taking some text from quotes that have been posted on Instagram as learning media outside of school. Keyword: Vocabulary Self-collection Strategy, Instagram, Survival Vocabulary, Students’ Perception